By the United States in Congress assembled. Proclamation : At all times it is our duty to acknowledge the over-ruling providence of the great Governor of the Universe ... recommend, that Thursday the third day of May next, may be observed as a day of humiliation, fasting, and prayer ... Done in Congress, the twentieth day of March ... one thousand seven hundred and eighty-one . (Printed by Timothy Green, printer to the governor and Company, 1781)
April 6, 1781 broadside of the proclamation by Governor John Turnbull of Connecticut, at the direction of the United States Congress, proclaiming May 3rd as a day of fasting and prayer because of the war and other domestic problems.